ICOS ATC CO Release from Svartberget (150.0 m) - Eric Larmanou; Per Marklund; Mikaell Ottosson-Löfvenius; Paul Smith (Integrated Carbon Observation System, 2025)
Quality-controlled data on molar fraction of atmospheric CO
Instrument Id 464: H2O correction updated. An interpolation over time of the water vapor correction factors has been applied up to 2020-02-20. Instrument Id 1399: H2O correction updated. An interpolation over time of the water vapor correction factors has been applied up to 2023-06-13
Larmanou, E., Marklund, P., Ottosson-Löfvenius, M., Smith, P. (2025). ICOS ATC CO Release from Svartberget (150.0 m), 2017-06-01–2025-03-31, ICOS RI, https://hdl.handle.net/11676/sWfTdyd6r_s6FVQPcaqwR3mm
Keywords: Atmosphere Thematic Centre; CO; ICOS; dry air mole fraction; time instant, UTC; time instant, UTC; quality flag; quality flag; number of points; number of points; standard deviation of gas mole fraction; standard deviation of gas mole fraction; CO (dry air mole fraction); CO (dry air mole fraction); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap